Who is eligible to obtain micro financing from Islamic banks?a case study of Pakistan? - Abbas, Kausar; Abdul Razak, Dzuljastri (2014)
This paper raises some concerns about the eligibility of obtaining micro financing from the Islamic banks. Do they have similar approach as in mostly conventional banks which make poor or low-income people not credit worthy or bankable? In order to achieve the objective of this study, a survey of 270 micro-entrepreneurs was conducted in three major cities of Pakistan namely Rawalpindi, Lahore and Peshawar.The result indicated an overwhelming majority of respondents who applied in Islamic banks were rejected. This indicate issues faced by micro-entrepreneurs who have business experiences, good attitude towards work and high moral principles but these criteria are insufficient for the banks to consider. The study further highlights that the fundamental principle of Islamic microfinance is the submission of Islamic values to promote social justice for all and emphasizes on the content of moral, economic and social aspect,although, it requires more attention. As such, there is a need for Islamic banks to look into their existing business model and diversify their products that can cater for the needs of micro-entrepreneurs in order to fulfill the Maqasid Al-Shariah